Phenomenologically separating nature from us: the role of nature in relation to human capabilities and environmental value - Watters, Andrew, author; Shockley, Kenneth, advisor; Cafaro, Philip, advisor; Scott, Ryan, committee member (Colorado State University. Libraries, 2022)
The role of nature in human well-being is often left unrecognized. In Thinking like a Mall, Steven Vogel provides a materialist argument that as humans we are always already engaged in a world that we have helped transform through our practices (our active and concernful involvement), and so it makes no sense to think of nature as something independent of us. I argue, drawing from the work of Merleau-Ponty and Heidegger, that while we are a part of Nature understood as a totality of things given that we are embodied-in-the-world, we are distinct from Nature insofar as we are concerned about our capabilities; our phenomenological concerns not being reducible to a thing-in-the-world. While the interconnection of things-in-the-world enable our capabilities given that we are embodied-in-the-world, they do so beyond our concerns. Hence, while we are part of Nature, there is a sense in which it is independent from us insofar as it contributes to our capabilities or practices independently of our knowledge; paralleling Breena Holland's characterization of the environment as a meta-capability with objective instrumental value. In addition to having objective instrumental value, it is shown through the work of Simon P. James and Kenneth Shockley that environmental features can have constitutive value and non-projected generative value. Insofar as we value our capabilities, we ought to protect the environment that makes them possible, recognizing that the environment enables our capabilities, in part, independently of our concerns.
Keywords: capabilities approach; embodiment; phenomenology; constitutive value; built environment; environmental value